The effect of piezoelectric actuation on stress distribution in aluminum plate with circular hole - Abuzaid, Ahmed; Shaik Dawood, Mohd. Sultan Ibrahim; Hrairi, Meftah (Asian Research Publishing Network (ARPN), 2015)
Structures with holes have been widely used in engineering designs. However, these structures have the tendency to develop critical crack growth because of stress concentration. This paper investigates the stress concentration factor (SCF) of an aluminum plate with circular hole and adhesively bonded piezoelectric actuator above the hole. The plate was subjected to uniaxial remote tensile stress while the actuator was excited with different voltages. The effect of the piezoelectric excitation on the stress in the host plate was analyzed using the finite element method (FEM). The stress distribution was evaluated by the stress concentration factor as an effectiveness criterion. The results indicated that the SCF is strongly affected by the applied voltage. Negative voltage tends to increase the SCF while the positive voltage tends to reduce the SCF. However, these effects are also dependent on the hole diameter and the size of the actuator.